Analysis the Impact of Bridges Existance for the Segamat River Using Infowork RS. Issue 1 (July 2016) - Adnan, M S; Ali, N C; Erfen, Y; Rahmat, S N; Razi, M A M; Musa, S
Abstract: Malaysia is experiencing two monsoonal seasons, which have induced heavy rainfall. The increasing of rainfall intensity and longer duration of rainfall has caused a flood. In 2007, Segamat city was hit by the flood due to increasing of rainfall and this has caused a huge damage in term of infrastructure as well as human life. Thus, this study was carried out with the aims to analyze the flood and develop a flood map for the Segamat River. The hydrological data, such as rainfall and streamflow data were retrieved from the Department of Irrigation and Drainage Malaysia (DID). While, for map preparation such as base map, landuse map and river map were delineated based on the topography map. Additionally, contour map was obtained from MACGDI. InfoWork River Simulation (RS) software was used for analysis and develops the flood map. Moreover, two scenarios were carried out to determine the effect of hydraulic structure presence in the waterway. The first scenario is the flood map without a bridge, while the second scenario is the flood map with a bridge. Based on the results, it clearly shows that the flood map with a bridge has higher flow, velocity and water table compared to the flood map without a bridge. In addition, a flood-prone area based on the developed map was identified. Thus, the generated flood map could serve important information to related agency in proposing a suitable design the mitigation works for this area.